Analisis Efektivitas Safety Awareness sebagai Syarat Tim Terhadap Pelanggaran Keselamatan Kerja di Yia dengan Cipp - Auliya Yazmin Rafasia; Irwina Meilani (UNIVERSITAS MARITIM AMNI SEMARANG, 2025)
This study aims to evaluate the effectiveness of the Safety awareness program as a requirement for issuing and renewing Driving Permits (TIM) for airside personnel at Yogyakarta International Airport (YIA). The program is designed to enhance personnel awareness of work safety to reduce operational violations in the airside area. A qualitative approach was used, employing the CIPP (Context, Input, Process, Product) evaluation model. Data were collected through interviews, observations, and documentation, and analyzed using the Miles & Huberman model. The findings indicate that the Safety awareness program is contextually relevant but faces weaknesses in input, such as non-interactive training methods and underutilized training facilities. The implementation process is inefficient due to the lack of monitoring systems and unstructured training schedules. Furthermore, the program has not fully succeeded in building a strong safety culture, as safety violations by personnel still occur. The study recommends improvements in training methods, regular post-training evaluations, and stronger supervision to enhance the program’s overall effectiveness.